Mortalidade de mulheres por agress\~oes no Brasil: Perfil e estimativas corrigidas (2011-2013) - Leila Posenato Garcia; Gabriela Drummond Marques da Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– Violence against women is a problem of great magnitude and relevance in Brazil, which has death as its more extreme expression. This study aimed to estimate corrected female mortality rates due to assault and to describe the profile of these deaths in Brazil, in its macro-regions and Federative Units (UF) in the period 2011-2013. Data from the Mortality Information System (SIM), of the Secretariat of Health Surveillance, Brazilian Ministry of Health (SVS/MS) were used. In Brazil, in the period 2011-2013, there were estimated 17,581 deaths of women for assaults, which correspond to a corrected annual mortality rate of 5.87 deaths per 100,000 women. In the studied period, there were, on average, 5,860 deaths of women from assault each year, 488 every month 16.06 each day, or one every 1h30m. The study confirmed that the mortality of women by assault is high in Brazil and affects women of all ages, ethnicities and levels of education. The main victims were adolescents and young women (45% in the age group 10-29 years), women with black skin color (64%) and residents in the Midwest, Northeast and North regions. The death's profile, with high occurrence inside households (28.1%) and during weekends (35.7%) is suggestive of domestic violence against women. In addition to presenting current data on mortality of women due to assaults, the study contributes to unveil the relative invisibility of the problem of violence against women in Brazil and discusses the need for improvement of fatal violence monitoring, as well as targeted actions and policies to deal with the problem.
Keywords: I12; 330; violence against women; mortality; descriptive epidemiology; Brazil